Peran Guru PAI Dalam Membentuk Karakter Kreatif Siswa melalui P5 (Projek Penguatan Profil Pelajar Pancasila) - Laysa Zahran; Tutut Handayani; Ani Marlia; Lutfiyani, Lutfiyani; Anggara, Baldi; Nuryanti, Eva (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2025)
This study aims to analyze the role of Islamic Education (PAI) teachers in shaping students’ creative character through P5 activities at SMPN 10 Palembang.aims to analyze the role of Islamic Education (PAI) teachers in shaping students’ creative character. Data collection efforts were carried out through observation, interviews, and documentation. Once the necessary data was obtained, the researcher conducted data analysis to derive research findings. This process involved data reduction, followed by data display, and finally, drawing conclusions based on all the data collected. The validity of the data was ensured through support from relevant sources, making this study a qualitative research. This research is based on Role Theory proposed by Aris Adi Laksono and Creativity Theory by Drevdal. Based on the research findings obtained through the data collection and analysis process following established procedures, the researcher found that the role of PAI teachers in shaping creative character through P5 activities is highly significant. As coordinators and facilitators, PAI teachers design and implement activities that cultivate students' character, particularly their creativity. In this character-building process, PAI teachers provide encouragement, motivation, and guidance to help students complete their project tasks effectively. Additionally, they instill a fundamental understanding that Islamic teachings serve as the foundation for actions. As a result, the students' creative ideas and works are expected to be beneficial for themselves and their surroundings.